MENINGKATKAN PRESTASI BELAJAR SISWA DENGAN PEMBELAJARAN STAD PADA PEMBELAJARAN IPS SISWA KELAS IV MIN MANISREJO KOTA MADIUN - Moh Rifai (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2014)
This research aims to improve student achievement by improving the learning process using methods that make students more active in participating on social studies and improve the quality of teachers in the subject of social studies at MIN Manisrejo. This study uses a class action research design composing of two cycles and pre-action. In each cycle has steps of planning, action, observation and reflection. Research subjects used are IVC grade students of MIN Manisrejo consisting of 28 students. Learning model used is STAD, which is in collaboration with a social studies teacher IVC grade of MIN Manisrejo. The results showed that the STAD can be used as a means to increase student achievement in describing an overview of natural disasters in social studies, namely the average total score of 47.87 in the pre-action increased to 61.87 in the first cycle which uses only media images and the second cycle which uses STAD increased 74.8. Learning at the pre-action is considered ineffective, while the first cycle that uses media images is considered effective enough. The first cycle that uses STAD is considered very effective. Based on the research results, it can be suggested that in social studies learning at IV grade of MIN Manisrejo especially in subjects describing the causes of natural disasters using STAD. In addition, the results of study can also be used as guidelines for further research. Keywords: Achievement, STAD Learning